1996
DOI: 10.1002/bit.260500202
|View full text |Cite
|
Sign up to set email alerts
|

Production and isolation of chitosan by submerged and solid-state fermentation fromLentinus edodes

Abstract: A method for the laboratory-scale production and isolation of chitosan (polyglucosamine) by liquid and solidstate fermentation from Lentinus edodes was developed. The yields of isolated chitosan were 120 mg/L of fermentation medium under liquid fermentation conditions and 6.18 g/kg of fermentation medium under solid-state fermentation conditions. The latter method, which gives up to 50 times yields than other chitosan production methods from fungi, provides a new flexible and easily scaledup procedure for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 8 publications
5
53
0
1
Order By: Relevance
“…It was observed that the yield of chitosan obtained from fungal mycelia grown in SSF (3.7 g chitosan/kg of solid substrate) was higher than that in SMF (0.6 g chitosan/L of fermentation medium) due to the low amount of mycelia produced in SMF (Nwe et al, 2002). Based on the results obtained from our research and Crestini et al, 1996, solid substrate fermentation was selected as the best fermentation method to produce chitosan by fungus Gongronella butleri (Figure 1). Fig.…”
Section: Growth Of Fungus and Extraction Of Chitosan By Traditional Msupporting
confidence: 53%
See 3 more Smart Citations
“…It was observed that the yield of chitosan obtained from fungal mycelia grown in SSF (3.7 g chitosan/kg of solid substrate) was higher than that in SMF (0.6 g chitosan/L of fermentation medium) due to the low amount of mycelia produced in SMF (Nwe et al, 2002). Based on the results obtained from our research and Crestini et al, 1996, solid substrate fermentation was selected as the best fermentation method to produce chitosan by fungus Gongronella butleri (Figure 1). Fig.…”
Section: Growth Of Fungus and Extraction Of Chitosan By Traditional Msupporting
confidence: 53%
“…Tan et al, 1996 evaluated the yield of chitosan from several Zygomycetes fungi including Absidia, Gongronella, Mucor and Rhizopus and concluded that G.butleri gave the highest yield of chitosan. At the same time, Crestini et al, 1996 reported that the yield of chitosan produced from Lentinus edodes grown in solid state fermentation, 6.18 g/kg was higher than that in submerged fermentation, 0.12 Production of Fungal Chitosan by Enzymatic Method and Applications in Plant Tissue Culture and Tissue Engineering: 11 Years of Our Progress, Present Situation and Future Prospects 137 g/l. In 1998, fungus Gongronella butleri was selected to produce chitosan in our research.…”
Section: Growth Of Fungus and Extraction Of Chitosan By Traditional Mmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the global chitinous waste production from this source is 2.1-2.7 Mt, most of which could be productively utilised in agriculture. While attempts have been made to extract chitin from the waste produced from edible fungi cultivation [12,13] or by using fungi to ferment plant material [14], these enterprises are currently conducted on a much smaller scale to crustacean-derived chitin production.…”
Section: Chitin Biochemistry and Productionmentioning
confidence: 99%